The Effect of Workload, Career Development and Work Discipline on Employee Performance at Asia Energy Transformation Foundation - Melisa Indah Sari; Herry Krisnandi; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to analyze the influence of Workload, Career Development, and Work Discipline on Employee Performance at the Asia Energi Transformation Foundation. The sample in this study were 109 respondents based on the Yamane formula. This study uses primary data with data collection methods through questionnaires distributed to 109 respondents. The data analysis technique uses inferential analysis with multiple linear regression. The results obtained in this study are workload has a positive effect on employee performance, career development has a positive effect on employee performance, and work discipline has a positive effect on employee performance. Therefore the Foundation must pay more attention to what employees need so that employee performance remains at a good level.